Correlation Patterns Among B7 Family Ligands and Tryptophan Degrading Enzymes in Hepatocellular Carcinoma - Chinnadurai, Raghavan; Scandolara, Rafaela; Alese, Olatunji B.; Arafat, Dalia; Ravindranathan, Deepak; Farris, Alton B.; El-Rayes, Bassel F.; Gibson, Greg (Frontiers in Oncology, 2020)
Mechanisms of dysfunctional T cell immunity in Hepatocellular Carcinoma(HCC) need to be well defined. B7 family molecules provide both co-stimulatory and co-inhibitory signals to T cells while tryptophan degrading enzymes like Indoleamine 2,3 dioxygenase(IDO) and Tryptophan 2,3 Dioxygenase(TDO) mediate tumor immune tolerance. It is necessary to identify their in situ correlative expression, which informs targets for combined immunotherapy approaches. We investigated B7 family molecules, IDO, TDO and immune responsive effectors in the tumor tissues of patients with HCC (n=28) using a pathway-focused quantitative nanoscale chip real-time PCR. Four best correlative expressions, namely (1) B7-1 & PD-L2, (2) B7-H2 & B7-H3, (3)B7-2 & PD-L1, (4)PD-L1 & PD-L2, were identified among B7 family ligands, albeit they express at different levels. Although TDO expression is higher than IDO, PD-L1 correlates only with IDO but not TDO. Immune effector (Granzyme B) and suppressive (PD-1 and TGF-β) genes correlate with IDO and B7-1, B7-H5, PD-L2. Identification of the in situ correlation of PD-L1, PD-L2 and IDO suggest their cumulative immuno suppressive role in HCC. The distinct correlations among B7-1, B7-2, B7-H2 and B7-H3, correlation of PD-1 with non-cognate ligands such as B7-1 and B7-H5, and correlation of tumor lytic enzyme Granzyme B with IDO and PD-L2 suggest that HCC microenvironment is complexly orchestrated with both stimulatory and inhibitory molecules which together neutralize and blunt anti-HCC immunity. Functional assays demonstrated that both PDL-1 and IDO synergistically inhibit T cell responses. Altogether, the present data suggest the usage of combined immune checkpoint blocking strategies targeting co-inhibitory B7 molecules and IDO for HCC management.